The ECHR Preamble vs. the European Arrest Warrant: balancing Human Rights protection and the principle of mutual trust in EU Criminal Law? - Daminova, Nasiya Ildarovna (Review of European and Comparative Law, 2022)
As stated in the European Convention on Hu- man Rights Preamble, the aim of the Council of Europe is the achievement of greater unity between its members through the maintenance and realisation of Human Rights and Fundamental Freedoms . Nowadays, the European Union includes the majority of the ECHR signatories (27 of 47) and incorporates the key legal instrument of judicial cooperation in criminal matters, namely the European Arrest Warrant Framework Decision . Nevertheless, the possible effects of the EAWFD on the practice of the European Court of Human Rights remain understudied – despite the crucial need to properly balance the enforcement of the principle of mutual recognition and Human Rights protection in the European Union. Since the first attempts to approach the EAWFD, the Strasbourg Court preferred to find the applications inadmissible (Pianese, Monedero Angora, Stapleton) or to establish a very high threshold for establishing a Convention violation within this context (Pirozzi). It will be argued that the newly developing Strasbourg Court’s case-law on the EAWFD (Castano, Bivolaru/Moldovan, Alosa) could potentially mark a new step in the judicial dialogue be- tween two European Courts. In the Castano and Bivolaru/ Moldovan rulings, the ECtHR – for the first time – found that the EU Member States had breached their obligations under Arts . 2 ( ́right to life ́) and 3 ( ́prohibition of torture ́) ECHR within the European Arrest Warrant context (murder/traffick- ing in human beings charges). At the same time, this interpre- tation opens the floor for discussion on potential applicability of other Convention provisions (Arts . 4, 5, 8, 13) to other offences listed in Art . 2(2) of the EAWFD (such as, for instance, corruption, fraud, computer-related crime etc .). Even though the Strasbourg Court has transposed the CJEU’s benchmarks of the EAW refusals legality assessment – i .e . a risk of inhuman or degrading treatment in the requesting State (Aranyosi/Căldăra ru), the EU Member States ́ courts are now forced – de facto – to consider an additional (ECHR-based) criterion for assessing the legality of refusals to execute the European Arrest Warrants. This can arguably pose further questions upon the entry into force of Protocol No. 15 ECHR which aims at the most effective realisation of the ́subsidiarity ́ principle in the European Convention system.